Noncommunicable diseases and the use of health services: analysis of the National Health Survey in Brazil - Deborah Carvalho Malta; Regina Tomie Ivata Bernal; Margareth Guimarães Lima; Silvânia Suely Caribé de Araújo; Marta Maria Alves da Silva; Maria Imaculada de Fátima Freitas; Marilisa Berti de Azevedo Barros
ABSTRACT OBJECTIVE To assess whether sex, education level, and health insurance affect the use of health services among the adult Brazilian population with chronic noncommunicable diseases (NCD). METHODS Data from a cross-sectional survey were analyzed, the National Health Survey (PNS). Frequency of use of services in the population that referred at least one NCD were compared with the frequency from a population that did not report NCD, according to sex, education level, health insurance, and NCD number (1, 2, 3, 4, or more). The prevalence and prevalence ratios were calculated crude and adjusted for sex, age, region, and 95% confidence intervals. RESULTS The presence of a noncommunicable disease was associated with increase in hospitalizations in the last 12 months, in 1.7 times (95%CI 1.53-1.9). Failing to perform usual activities in the last two weeks for health reasons was 3.1 times higher in NCD carriers (95%CI 2.78-3.46); while the prevalence of medical consultation in the last 12 months was 1.26 times higher (95%CI 1.24-1.28). NCD carriers make more use of health services, as well as women, people with higher number of comorbidities, with health insurance, and higher education level. CONCLUSIONS NCD carriers make more use of health services, as well as women, people with higher number of comorbidities, with health insurance, and higher education level.